1994
DOI: 10.1016/0266-7681(94)90069-8
|View full text |Cite
|
Sign up to set email alerts
|

Can Sensory and Motor Collateral Sprouting be Induced from Intact Peripheral Nerve by End-to-Side Anastomosis?

Abstract: The possibility that collateral sprouting could occur from intact axons in an undamaged sciatic nerve was studied in the rat by suturing either a 7-day predegenerated or a fresh nerve segment in an end-to-side fashion to the sciatic nerve proper. Following a 14- or 35-day recovery period, the pinch reflex test was performed on the transplanted segment to demonstrate the presence of sensory axons. The majority of cases, using a predegenerated nerve segment but not a fresh segment, responded positively. Neurofil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
189
1
14

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(214 citation statements)
references
References 23 publications
10
189
1
14
Order By: Relevance
“…This is an issue whether axons regenerate into the recipient limb as collateral sprouts in response to diffusible factors (Lundborg, et al 1994), or as regenerative sprouts in response to injury. Our data showed that axons rapidly regenerated into the ETS repair following epineurotomy, and by 60 days reached motor targets ~3.1 cm away (median length 2.3 cm).…”
Section: Discussionmentioning
confidence: 99%
“…This is an issue whether axons regenerate into the recipient limb as collateral sprouts in response to diffusible factors (Lundborg, et al 1994), or as regenerative sprouts in response to injury. Our data showed that axons rapidly regenerated into the ETS repair following epineurotomy, and by 60 days reached motor targets ~3.1 cm away (median length 2.3 cm).…”
Section: Discussionmentioning
confidence: 99%
“…51 Accordingly, the number of nerve fibers entering the recipient nerve from the mixed donor nerve was higher after making either an epineurial or perineurial window than after the nerve coaptation with epineurial suturing only, resulting in more effective muscle reinnervation during the first 3 months after end-to-side nerve coaptation. 12,13,29,[48][49][50]54 but not later from 4 up to 8 months after surgery. 16,51,53,64 Interestingly, if epineurial or perineurial windows were enlarged from 1 to 4 or 5 mm, respectively, then, also, the magnitude of axonal ingrowth into the recipient nerve was increased.…”
Section: Kovač Ič Et Almentioning
confidence: 91%
“…[1][2][3][4][5][6] Functional motor and sensory reinnervation of target tissue was observed after such nerve repair in experimental mammals. [7][8][9][10][11][12][13][14][15][16] Also, several clinical case series suggest that some patients with extensive nerve injuries in the upper extremity, facial palsy, or neurinoma could benefit by such a treatment, although the results are quite unpredictable. 2,[17][18][19][20][21][22][23][24][25][26][27][28] The basic idea of end-to-side nerve coaptation is to achieve reinnervation of a denervated tissue by the collateral sprouting of uninjured axons from the donor nerve through the distal stump of the injured recipient nerve without sacrificing the innervation of the original targets of the donor nerve.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in neuroscience and cognitive science have opened new possibilities for the future to improve sensory recovery after nerve repair, especially with respect to functional sensibility and, specifically, the capacity for identification and discrimination of touch (Lundborg, 1994;.…”
Section: Introductionmentioning
confidence: 99%